The Effect of Ginger Aromatherapy and Warm Compresses on Primary Dysmenorrhea in Adolescent Girls - Gultom, Okto Riristina; Hamisah, Hamisah; Mawwadah, Sofia; Hatini, Erina Eka (Rifa'Institute, 2026)
Overview: Dysmenorrhea is the term for severe lower abdominal pain brought on by greater uterine contractions. 64.25% of Indonesian women experience dysmenorrhea, yet many choose not to receive the recommended care. Non-pharmacological treatments, such as warm compresses and ginger aromatherapy, are safer possibilities. Objective: This study aims to find out how ginger's aromatherapy and warm compression affected primary dysmenorrhoea in adolescent girls Method: Thirty teenage females with primary dysmenorrhea at SMK Muhammadiyah Palangka Raya participated in this quasi-experimental study. Both pre-test and post-test designs were employed. The sample was chosen and split into two intervention groups using the purposive sampling technique. The Numeric Rating Scale (NRS) was used to test the pain intensity data. The Shapiro-Wilk, Paired Sample t-Test, and Independent Sample t-Test were used to test the analysis results. Outcomes: The results of the study show that there were differences in primary dysmenorrhea pain levels before and after the intervention. The average pain level was 2.71 (SD = 1.069) for the ginger aromatherapy group and 4.07 (SD = 1.385) for the warm compress group, with a p-value of 0.007 (p < 0.05). Conclusion: demonstrates that ginger aromatherapy is more effective than warm compresses for reducing primary dysmenorrhea